Enhancing regular monitoring of food-contact surface hygiene with rapid microbial kits - Saad, Mazni; See, Toh Poh; Abdullah, Mohd Faiz Foong; Md. Nor, Norazmir (AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK, 2018)
To ensure that food is always healthy and safe, food business operators utilize a simple and practical method of identifying and verifying microbes. This study looks at the practicality of an inexpensive and user-friendly microbial kit that evaluates the cleanliness level of 72 samples of food-contact surfaces (FCS) of food service establishments in two states of Malaysia. It detected 70% coliform contamination which suggests that food service operators may need to improve the cleanliness of FCS. It can be concluded that the microbial kit used is a practical self-check approach for determining the hygiene level of any food service operation and should be made mandatory.